Variability of turbulent mixing observed by high-resolution Acoustic Doppler Current Profilers in the deep South China Sea - Hao Xun; Chun Zhou; Chun Zhou; Chun Zhou; Xin Xiao; Shoude Guan; Shoude Guan; Shoude Guan; Xiaodong Huang; Xiaodong Huang; Xiaodong Huang; Tangdong Qu; et al. (Frontiers in Marine Science)
Despite its crucial role in sustaining the global meridional overturning circulation, turbulent mixing remains poorly observed, particularly in the deep ocean. We deployed 1200 kHz Acoustic Doppler Current Profilers (ADCPs) with high temporal [O(1 s)] and spatial [O(2 cm)] resolution to obtain continuous measurements of turbulent mixing at a depth of 1086 m in the northeastern South China Sea. Comparative experiments and the evaluation of four different analysis methods were conducted to determine optimal configurations and effective methodologies for continuous observations of turbulent mixing accompanied by background shear flow. Our observations revealed large temporal fluctuations in near-bottom turbulent kinetic energy dissipation rates, varying by up to two orders of magnitude within a single day. These fluctuations were primarily driven by shear instabilities associated with high-mode diurnal internal tides. These findings provide optimized observational strategies for deep-ocean turbulence studies and enhance our understanding of turbulent processes and their implications for large-scale oceanic dynamics.